Can the single-breath helium dilution method predict lung volumes as measured by whole-body plethysmography? - Coertjens, Patrícia Chaves (Sociedade Brasileira de Pneumologia e Tisiologia, 2013)

(untitled)
OBJECTIVE: To compare TLC and RV values obtained by the single-breath helium dilution (SBHD) method with those obtained by whole-body plethysmography (WBP) in patients with normal lung function, patients with obstructive lung disease (OLD), and patients with restrictive lung disease (RLD), varying in severity, and to devise equations to estimate the SBHD results. METHODS: This was a retrospective cross-sectional study involving 169 individuals, of whom 93 and 49 presented with OLD and RLD, respectively, the remaining 27 having normal lung function. All patients underwent spirometry and lung volume measurement by both methods. RESULTS: TLC and RV were higher by WBP than by SBHD. The discrepancy between the methods was more pronounced in the OLD group, correlating with the severity of airflow obstruction. In the OLD group, the correlation coefficient of the comparison between the two methods was 0.57 and 0.56 for TLC and RV, respectively (p < 0.001 for both). We used regression equations, adjusted for the groups studied, in order to predict the WBP values of TLC and RV, using the corresponding SBHD values. It was possible to create regression equations to predict differences in TLC and RV between the two methods only for the OLD group. The TLC and RV equations were, respectively, ∆TLC(WBP-SBHD) in L = 5.264 − 0.060 × FEV(1)/FVC (r(2 )= 0.33; adjusted r(2) = 0.32) and ∆RV(WBP-SBHD) in L = 4.862 − 0.055 × FEV(1)/FVC (r(2 )= 0.31; adjusted r(2) = 0.30). CONCLUSIONS: The correction of TLC and RV results obtained by SBHD can improve the accuracy of this method for assessing lung volumes in patients with OLD. However, additional studies are needed in order to validate these equations.